PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP KECEMASAN PADA WANITA PASANGAN USIA SUBUR (WPUS) PENDERITA HIV/AIDS - Novie E Mauliku; Siti Nur Endah; Sri Yuniarti (LPPM Universitas Abdurrab, 2021)
HIV / AIDS is an infectious disease that attacks the immune system. HIV / AIDS cases are still a health problem in the world, because the disease trend is still increasing. Negative stigma and discriminatory can cause high psychological distress and feelings of anxiety. Excessive anxiety will cause feelings of uncertainty, guilt, depression, and helplessness, anxiety, phobias, illusions and hallucinations, thus affecting the quality of life. This study aims to determine the effect of progressive muscle relaxation therapy on anxiety levels in women of reproductive age couples (WPUS) with HIV / AIDS. The research method used a quasi-experimental with One group pretest-posttest design. The sample was 10 people with HIV / AIDS. Data obtained using HARS and analyzed the T-dependent test with a significance test of p value 0.05 (95% CI). The results showed that the average anxiety index before progressive muscle relaxation therapy was 29.90 (severe anxiety), the average anxiety index after progressive muscle relaxation therapy was 16.50 (mild anxiety). The results of the analysis showed that there was an effect of progressive muscle relaxation therapy on the anxiety level of WPUS suffering from HIV / AIDS (p Value = 0.000). It is hoped that this progressive muscle relaxation therapy can be used to reduce the anxiety level of women of reproductive age couples (WPUS) suffering from HIV / AIDS through health education and demonstration of progressive muscle relaxation therapy movement.